Library Transformation Based on Social Inclusion in the Balai Buntar Village Library Central Bengkulu (Open Society Conference, 2024)
The Balai Buntar village library as an educational institution for the Pondok Kelapa village community in Central Bengkulu has the aim, function and role of a library based on social inclusion. The library plays an active role in community empowerment in the development of Pondok Kelapa village. This research aims to determine the transformation of social inclusion-based libraries at the Balai Buntar village library in empowering the Pondok Kelapa village community. The research method used is a qualitative research method with a case study approach, data collection techniques used are interviews and literature studies, the data that has been obtained is analyzed using the data reduction stage, display data, and conclusion drawing. The research results show that the Balai Buntar village library plays an active role as an inclusive space in supporting the local potential of the Pondok Kelapa village community. Various programs were created to facilitate public education in the fields of agriculture, plantations and crafts which were developed creatively and innovatively by library managers. Partnerships are carried out in various ways stakeholder, both from the village and outside the village collectively in community empowerment. The conclusion of this research is that the Pondok Kelapa village community received the impact of social inclusion-based library transformation from the Balai Buntar village library by increasing community welfare in social, educational and economic aspects by utilizing the resources of various sectors to become economic capital, and increasing knowledge through facilitated collections. Balai Buntar village library.